Lymphocytic interstitial pneumonia in a patient with lymphocytic colitis - Chojnacki, Cezary; Knopik-Dąbrowicz, Alina; Mania, Dorota; Chojnacki, Jan (Gastroenterology Review/Przegląd Gastroenterologiczny, 2022)
The course of lymphocytic colitis (LC) is usually mild with periods of exacerbation and remission. Chronic non-bloody diarrhoea [1] dominates. In recent years significant findings with respect to the association of the gut intraepithelial lymphocytes (IELs) and various diseases have been observed [2]. We report the cause of LC with coexistence of severe lymphocytic interstitial pneumonia (LIP).